Retorica e mito in Giambattista Vico - Gualtieri, Gaetano Antonio <1960> (Alma Mater Studiorum - Università di Bologna, 2011)
The purpose of this thesis is to show that Vico had the constant aim, remained unaltered in time, to support the usefulness of Rhetoric. The awareness of the strength acquired by the “anti-rhetorical” movements, particularly by the Cartesians and the Logicians from Port-Royal, obliged Vico to elaborate some strategies and counter-moves that, little by little, became more and more complex and refined, till they inspired his main work, The New Science. By taking into consideration the most significant aspects of Vico’s speculation (topic, tropes, the formation of language, the development of human thought, the new conception of philology ), this work shows that they are part of a strategy worked out by the Neapolitan philosopher, in order to demonstrate the validity, the usefulness and the modernity of Rhetoric. Every aspect of Vico’s thought reaches its peak when Vico formulates his theory about myths, which he interprets as an expression of the primitive man’s necessities and demands. The point of view expressed by this doctorate thesis emphasizes that, despite the inevitable modifications that have taken place through the centuries, Vico’s thought keeps its substantial unity. So those subjects that critical literature tends to separate are, in reality, linked and unified.